Political economy of national agricultural statistics: The case of Niger - Benin, Samuel; Babu, Suresh Chandra; Odjo, Sunday P.; Gado, Aissata Abdou; Paul, Namita (International Food Policy Research Institute, 2020)
This paper conducts a political economy analysis to understand the factors that affect provision of and access to reliable agricultural statistics and data systems in Niger. A conceptual framework that identifies selected political economy aspects including political will, transparency and accountability, state capacity, and international commitments is developed. The predictions of the framework are tested using information collected through informal and formal interviews with professionals and staff of different institutions and organizations that provide or use agricultural statistics to analyze how different components of agricultural statistics and the underlying capacity and systems are differentially influenced by various political-economy factors. Implications for Niger and at the global level for developing an effective strategy to improve agricultural statistics and data (availability, quantity, and quality) that go beyond technological and methodological fixes are drawn.